2008
DOI: 10.1021/jf8008926
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation of the Chloroplast trnL (UAA) Intron Polymorphisms for the Authentication of Plant Oils by Means of a Lab-on-a-Chip Capillary Electrophoresis System

Abstract: Methods to discriminate plant oils facilitate the detection of either deliberate or accidental adulteration. To this direction, the variability in length among plant species of the chloroplast trnL intron was exploited for the authentication of edible and cosmetic plant oils, with an extra emphasis on olive oil. The methodology was based on the combinatorial use of a PCR assay with a capillary electrophoresis system such as the lab-on-a-chip technology. Application of the assay on DNA extracted from different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 26 publications
2
34
0
1
Order By: Relevance
“…Moreover, barcode size did not vary among the five olive cultivars, providing proof of the species specificity of trnL (UAA) intron length polymorphisms. Our results were in agreement with Spaniolas, Bazakos, Awad, et al (2008), Spaniolas, Bazakos, Spano, et al (2010), who demonstrated length polymorphisms of the barcode amplicon among olive, soybean, sunflower, sesame, cotton, corn and hazelnut. Barcode fragment length polymorphisms among olive and the remaining four oil seed species (palm, rapeseed, peanut and safflower) are shown for the first time in the present research.…”
Section: Pcr-ce Analysis Of Reference Tissue and Oil Samplessupporting
confidence: 93%
See 3 more Smart Citations
“…Moreover, barcode size did not vary among the five olive cultivars, providing proof of the species specificity of trnL (UAA) intron length polymorphisms. Our results were in agreement with Spaniolas, Bazakos, Awad, et al (2008), Spaniolas, Bazakos, Spano, et al (2010), who demonstrated length polymorphisms of the barcode amplicon among olive, soybean, sunflower, sesame, cotton, corn and hazelnut. Barcode fragment length polymorphisms among olive and the remaining four oil seed species (palm, rapeseed, peanut and safflower) are shown for the first time in the present research.…”
Section: Pcr-ce Analysis Of Reference Tissue and Oil Samplessupporting
confidence: 93%
“…Interspecific length polymorphisms in the plastid trnL (UAA) intron were previously proposed for botanical origin authentication in plant oils (Spaniolas, Bazakos, Awad, et al, 2008;Spaniolas, Bazakos, Spano, et al, 2010). However, the applicability of a barcode amplicon size separation assay to discriminate species-specific fragments in oil blends was not investigated.…”
Section: Pcr-ce Analysis and Fatty Acid Profiling Of Plant Oil Admixtmentioning
confidence: 99%
See 2 more Smart Citations
“…(Consolandi et al, 2008) DNA recovery methods from olive oil have been developed by many authors (Busconi et al 2003;Doveri et al 2006;Pasqualone et al 2007;Consolandi et al 2008). Several commercial kits, providing adapted protocols, were used in different works (Martins-Lopes et al 2008;Spaniolas et al 2008a;Ayed et al 2009;Pafundo et al 2010). All of these studies confirmed that the DNA of the cultivars is recoverable from extra virgin olive oil, but it has low quantity and quality.…”
Section: Dna-based Markersmentioning
confidence: 95%